2021
DOI: 10.5530/ijpcs.2021.10.9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Pharmacists about Nuclear Pharmacy Services in Saudi Arabia

Abstract: Goal: The knowledge of nuclear pharmacy is essential in pharmacy practice. In addition, the nuclear pharmacy services demand various diagnoses and drug therapy management. In this study, we aimed to explore pharmacists' knowledge about nuclear pharmacy in the Kingdom of Saudi Arabia. Methods: This is a crosssectional qualitative study. In this study, we distributed an electronic validated reliability questionnaire to all pharmacists and pharmacy interns. Students were excluded from this study. The survey colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These findings are slightly different from the report of other studies. According to the survey by Alomi et al (2021a), Saudi Arabia pharmacists had poor knowledge of nuclear pharmacy practice. In a study conducted in Malaysia, India, Pakistan, Sri Lanka, Bangladesh, UAE and Nepal by Parasuraman et al (2014a), about 30% of health professionals were aware of the use of radiopharmaceuticals in the health sector.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are slightly different from the report of other studies. According to the survey by Alomi et al (2021a), Saudi Arabia pharmacists had poor knowledge of nuclear pharmacy practice. In a study conducted in Malaysia, India, Pakistan, Sri Lanka, Bangladesh, UAE and Nepal by Parasuraman et al (2014a), about 30% of health professionals were aware of the use of radiopharmaceuticals in the health sector.…”
Section: Discussionmentioning
confidence: 99%
“…The background training of the pharmacists and their cadre might have also contributed to the differences noted. In Saudi Arabia, many of the healthcare organisations have nuclear medicine headed by the consultant physician working in collaboration with nurses, pharmacists, and technicians ( Barnett & Kavula, 1992;Paez et al, 2016;Alomi et al, 2021a;Alomi et al, 2021b). Hospital pharmacists might have been slow in adding nuclear pharmacists to their staff and might have transferred such professional obligation to non-pharmacist personnel in the nuclear medicine domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] Additional research examined specific knowledge or perceptions regarding pharmaceutical care. [9][10][11][12][13] Numerous guidelines discussed the cross-sectional model in research practice and the model's advantages and disadvantages. [13][14][15][16][17][18][19][20][21][22] However, the policies and procedures for cross-sectional research are not well documented or are only found infrequently in the literature search database.…”
Section: Introductionmentioning
confidence: 99%